The Problem of the Status of Harmony in Pythagorean Philosophy - Świercz, Piotr (Horyzonty Polityki, 2020)
RESEARCH OBJECTIVE: The aim of this article is to analyze the ontic status of harmony in Pythagorean philosophy. THE RESEARCH PROBLEMS AND METHODS: The main problem undertaken in the article is an analysis of the ontic status of harmony in Pythagorean philosophy, conducted within the context of the theory of principles. The research method is based on an analysis of source texts. THE PROCESS OF ARGUMENTATION: The article begins with an analysis of passages from the works of Philolaus of Croton. Next, the treaty Peri archan attributed to Archytas of Tarentum is analyzed. The analysis of the source texts includes references to the main interpretative positions contained in the secondary literature. RESEARCH RESULTS: The most important result of the scientific analysis conducted here is the organization of the possible interpretations of the ontic status of harmony and indication of the main difficulties associated with them. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: In his conclusions, the author indicates interpretative possibilities resulting from the perspective taken in the article, as well as areas that require further study, concerning such issues as the relationship between Pythagorean and Orphic thought.